All around the year holidays and celebrations in American life - Santino, Jack (Univ. of Illinois Press, 1994)
"Whether decorating Easter trees, observing the New Year's Eve ritual of the Hungry Hog Society, or celebrating Wagner's birthday by incinerating a model of Valhalla on an outdoor barbecue to the closing strains of "Gotterdammerung," Americans combine the traditional and the offbeat as they create new holidays and celebrate old ones." "In All Around the Year, Jack Santino guides the reader through a variety of holidays, festivals, and life-cycle rituals and celebrations. Drawing from history, anthropology, popular culture, and folklore, Santino shows the intricate relationships between holidays and the roles of celebrations and rituals in people's lives. He combines scholarship, field research, and personal reminiscence in this highly readable account of a subject that constitutes a major dimension of our social lives. Nearly fifty illustrations depict holiday symbols and decorations both traditional and contemporary, from greeting cards to wreath-bedecked cars to restaurant menus."--BOOK JACKET.